(untitled) (Development Service Industry Management, 2025)
The article analyzes the factors influencing the physical and psycho-emotional state of individuals. It has been revealed that a significant number of people sustain injuries as a result of road accidents, natural disasters, armed conflicts, and industrial activities. All these factors considerably contribute to the spread of disability, which has become a pressing issue of the 21st century. In order to ensure higher-quality service for people with special needs within hotel enterprises, this study classifies the types of disabilities. Such classification provides a better understanding of the specific needs of each person depending on their type of disability and, in turn, facilitates the organization of service processes. Data analysis has shown that most hotels in Ukraine are not prepared to provide services for people with disabilities, both in terms of material resources and professional training. A conducted SWOT analysis clearly identified the strengths and potential risks in planning and organizing inclusive hotel services. Based on the results of the SWOT analysis, it was established that developing inclusive service systems has long-term prospects, expands the target audience, increases revenues, and enhances social responsibility, reputation, and customer loyalty of hotels. Therefore, a potential model for organizing inclusive hotel services was developed, and the measures that should be applied within hotel enterprises to create a high-quality inclusive environment were outlined.